2022
DOI: 10.1177/00031348221082288
|View full text |Cite
|
Sign up to set email alerts
|

“HYPER-EARLY” Tracheostomy within 48 hours has less Complications and Better Prognosis Compared to Traditional Tracheostomy

Abstract: Introduction Tracheostomies may be performed “early” or “late.” There is no agreement on the best timing for tracheostomy. This study compares tracheostomies and complications when performed within 48 hours with those performed from 48 hours to 21 days. Methods Patients who underwent tracheostomy in the 2017-2018 National Trauma Data Bank (NTDB) were categorized into 2 groups: early tracheostomy (≤48 hours) and late tracheostomy (>48 hours to 21 days). Primary outcome measured was mortality. Chi square mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…A Cochrane review from 2015 by Andriolo et al, did not suggest any mortality benefit or significant difference between ET and LT. 10 Other studies have demonstrated a possible benefit to ET performance in non‐COVID patients. 11 , 12 However, since the COVID‐19 pandemic, there has been much conflicting data within the literature. Ji et al performed the first systematic review on the timing of tracheostomy and clinical outcomes in COVID‐19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane review from 2015 by Andriolo et al, did not suggest any mortality benefit or significant difference between ET and LT. 10 Other studies have demonstrated a possible benefit to ET performance in non‐COVID patients. 11 , 12 However, since the COVID‐19 pandemic, there has been much conflicting data within the literature. Ji et al performed the first systematic review on the timing of tracheostomy and clinical outcomes in COVID‐19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…When aaplying definitions for early and late tracheostomy timing (14 days or 16.7 days as cut-offs) only 16.7 days cut-off reported differences in mortality being higher in the late group than the early tracheostomy group, not confirming the results of other meta-analyses [12][13][14]25 . An early tracheostomy performance demonstrated possible beneficial effects on outcome in non-COVID-19 patients 29,30 . However, this not really accounts for the real impact in terms of benefits or harm on patients' outcome, because of critically ill patients present a high likelihood of evolving to multiple organ dysfunction that cannot be optimally predicted during the first days of ICU admission 11 .…”
Section: Mortalitymentioning
confidence: 98%